2018
DOI: 10.1007/s10549-018-4677-2
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of quality of life following breast cancer diagnosis

Abstract: The majority of BCS report good QoL as they transition from treatment to survivorship. However, some women have persistently low QoL in each domain and some experience declines in emotional and/or social/family well-being. Psychosocial variables are consistently associated with improving and/or declining trajectories of physical/functional and emotional well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 44 publications
6
50
0
3
Order By: Relevance
“…Therefore, investigating HR-QoL by looking at average levels within the sample is not as useful as by investigating subgroups with distinct developmental trajectories of HR-QoL. Previous studies already identified several trajectories of HR-QoL in people during or after rehabilitation from breast cancer or stroke, which were related to the proposed characteristic trajectories of level of dysfunction: high, recovery, decline and low HR-QoL [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigating HR-QoL by looking at average levels within the sample is not as useful as by investigating subgroups with distinct developmental trajectories of HR-QoL. Previous studies already identified several trajectories of HR-QoL in people during or after rehabilitation from breast cancer or stroke, which were related to the proposed characteristic trajectories of level of dysfunction: high, recovery, decline and low HR-QoL [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of early screening skills and treatment modalities, patients with breast cancer have an increased survival rate (5‐year survival rates ranging from 58% to 90%) . However, following primary and complementary cancer treatment, patients with breast cancer often experience various treatment‐related adverse effects, such as various symptom clusters, psychological trauma and negative coping strategies, and overall health‐related quality of life impairment . These problems negatively affect patients' rehabilitation process, and patients have a myriad of unmet needs while confronting these problems …”
Section: Introductionmentioning
confidence: 99%
“…As an explanation, the assumption of differences between the patients might not serve well as a distinguishing rule for the purpose of instrument validity. Regardless of the fact that there is a general tendency toward reaching a satisfactory QoL over the course of time (24), a study revealed that there are some discrepancies among the patients in terms of the patterns of improvement in their QoL (25). These findings imply that the differences in the pattern of QoL improvement might blur the symptomatology included in FBSI index.…”
Section: Discussionmentioning
confidence: 99%